Comparison of computational efficiency of explicit and implicit schemes for the sediment transport problem in coastal zones - Sukhinov, A.I.; Protsenko, E.A.; Chistyakov, A.E.; Shreter, S.A. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2015)
An unsteady spatial two-dimensional sediment transport model in coastal zones is considered. The model takes into account the following physical parameters and processes: the soil porosity; the critical shear stress at which the sediment displacement begins; the turbulent exchange; the dynamically variable geometry of the bottom and the level elevation function; the wind flows; and the bottom friction. A spatial three-dimensional hydrodynamic model for coastal zones and a transport model for suspended particles are proposed and implemented on a computing cluster. Some numerical results are discussed.